Excess costs of multiple sclerosis: A register-based study in Sweden: Chantelle Murley. (25th October 2022) - Murley, C; Tinghög, P; Sebsibe Teni, FS; Machado, A; Alexanderson, K; Hillert, J; Karampampa, K; Friberg, E
Abstract: Background and Objective: Population-based estimates of the socioeconomic burden of multiple sclerosis (MS) are limited, especially regarding primary healthcare. This study aimed to estimate the excess costs of people with MS that could be attributed to MS, including primary healthcare. Methods: An observational study was conducted of the 2806 working-aged people with MS in Stockholm, Sweden and 28, 060 propensity score matched references without MS. Register-based resource use was quantified for 2018. Annual healthcare costs (primary, specialised outpatient, and inpatient healthcare visits along with prescribed drugs) and productivity losses (operationalised by sickness absence and disability pension days) were quantified using bottom-up costing. Costs were compared between the people with MS and references with independent t-tests with bootstrapped 95% confidence intervals (CIs) to isolate the excess costs of MS. Results: The mean annual excess costs of MS for healthcare were €7381 (95% CI: 6991-7816) per person with MS with disease modifying therapies as the largest component (€4262, 95% CI: 4026-4497). There was a mean annual excess cost for primary healthcare of €695 (95% CI: 585-832) per person with MS, comprising 9.4% of the excess healthcare costs of MS. The mean annual excess costs of MS for productivity losses were €13, 173 (95% CI: 12, 325-14, 019) per person with MS, predominately from disability pension (79.3%). Conclusions: The socioeconomic burden of MS in Sweden from healthcare consumption and productivity losses was quantified, updating knowledge on the cost structure of the substantial excess costs of MS. Key messages:  Primary healthcare contributes around a tenth of the excess healthcare costs of MS in Sweden, primarily owing to contacts with healthcare professionals other than physicians.  Overall, the excess costs of MS in Sweden from lost production are larger in magnitude than the excess costs for healthcare consumption.